Plataforma de investigación e innovación oológica en red regional: Plan parcial de bio-conservación urbana Choachí 2050 (2017)
Born the idea of a partial plan of Bio-Conservation in the city is born where it seeks to improve the environmental and socio-economic conditions of the municipality by means of renovation in the public space and a high environmental value in terms of its water sources. That is why a polygon of performance of 12 hectares was developed, where five units of action are proposed with equipment highly benefiting the municipality for its development and competitiveness for the region. On the other hand, taking into account the analysis of the structural systems of Choachí where it was possible to situate agricultural production as a vocation in development under urban guidelines and favorable for the municipality thanks to its high production in this poultry case, A unit of educational-investigative action, which aims to focus projects on research and innovation of highly agricultural technologies so that through this raw material give added value and generate a highly global economic development for the region.